First description of an IgM monoclonal antibody causing αIIbβ3 integrin activation and acquired Glanzmann thrombasthenia associated with macrothrombocytopenia. (19th April 2019) - Pillois, Xavier; Guy, Alexandre; Choquet, Émeline; James, Chloé; Tuffigo, Marie; Viallard, Jean‐François; Garcia, Cédric; Bordet, Jean‐Claude; Jandrot‐Perrus, Martine; Payrastre, Bernard; Fiore, Mathieu
Abstract : Essentials Acquired Glanzmann thrombasthenia (GT) is generally caused by anti‐αIIb β3 autoantibodies. We report the case of a man with an acquired GT phenotype associated with macrothrombocytopenia. Perturbed platelet function were associated with an activating anti‐αIIb β3 IgM autoantibody. This novel clinical entity raises interesting questions about the αIIb β3 integrin signaling. Summary: Background: Acquired Glanzmann thrombasthenia (GT) is a bleeding disorder generally caused by anti‐αII b β3 autoantibodies. Objectives: We aimed to characterize the molecular mechanism leading to a progressive GT‐like phenotype in a patient with chronic immune thrombocytopenia. Patient, Methods, and Results: The patient suffered from repeated episodes of gastrointestinal bleeding; further studies indicated a moderate platelet aggregation defect. A few months later, platelet function showed abolished aggregation using all agonists, but normal agglutination with ristocetin. No platelet‐bound antibodies were detected, but the presence of large amounts of an IgM type antibody detected together with αII b β3 in the patient permeabilized platelets suggested that this IgM was an autoantibody causing the internalization of the complex. This was confirmed by the fact that the patient IgM bound to normal platelets but not to platelets from GT type I patients. Moreover, patient′s plasma activated αII b β3 on controls' platelets as evidenced by increased PAC‐1 binding. We also demonstrated that the patient plasma triggered αII b β3 outside‐in signaling, as β3 Tyr773 and FAK were phosphorylated, and increased the rate of actin polymerization in resting platelets reflecting an impairment of cytoskeletal reorganization. Because different signs of dysmegakaryopoiesis were also observed in our patient, we evaluated the ability of its serum to impair proplatelets formation and showed that it significantly decreased the number of proplatelet‐bearing megakaryocytes in controls' bone marrow stem cells culture compared with normal serum. Conclusions: We present the case of a patient with a progressive and severely perturbed platelet function associated with the presence of an IgM activating autoantibody directed against αII b β3 .